A study on figurative non-verbal creativity by motor activation of left hand. - Cantú Cervantes, Daniel (Universidad Autónoma de Tamaulipas, 2019)
This study investigated the impact of the use of the left hand on the non-verbal figurative creativity test of Torrance in higher education students. The participants were 40 students of the Universidad Autónoma de Tamaulipas in the 2018-1 School Period, formed in four groups: 10 right-handed women (Age, M=23, SD= .816), 10 left-handed women (Age, M= 23.20, SD = 1033), 10 right-handed men (Age, M =23.20, SD= 1814) and 10 left-handed men (Age, M= 23, SD= 1155). The study leaned towards the quantitative approach with transectional design for observed the figurative creative performance during the use the predominant and nonpredominant hand in the tests. The results obtained show higher scores in all groups without gender distinction, when they used the left hand in the tests, although these differences were not significant (p> .05), with respect to when they used their right hand.